Experimental mechanics and materials selected, peer reviewed papers of the International Conference on Experimental Mechanics 2010 (ICEM10), 29 November - 1 December 2010, Legend Hotel Kuala Lumpur, Malaysia - Abdul Nassir Ibrahim (Applied mechanics and materials, 2011)
The 47 selected papers in this collection originally were presented during the International Conference on Experimental Mechanics 2010 held in Kuala Lumpur, Malaysia on November 29-December 1, 2010. Topics include, but are not limited to: crack tip shielding effect on fatigue crack propagation in porous silicon carbide, an experimental study on displacement and strain distributions of bone models with dental implants, high strain rate compressive stress-strain loops for structural adhesives, investigation of shrinkage in softwood using the digital image correlation method, and high velocity nano alumina wet milling in zirconia and corundum mills. Member guest editors are Ibrahim, Sulaiman, Abdullah, Yusof, Abas, and Yazid.